The Role of Light Program and Melatonin on Alleviation of Inflammation Induced by Lipopolysaccharide Injection in Broiler Chickens - Gehad, Ahmed E.; Mehaisen, Gamal M.; Abbas, Ahmed O.; Mashaly, Magdi M. (International Journal of Poultry Science, 2008)
Two experiments were conducted with male broiler chickens to study the effect of light program and melatonin injection on enhancing the immune response and reducing the inflammatory response induced by lipopolysaccharide (LPS) injection. In the first experiment, one-day-old broiler chicks were divided into two groups: The first group was exposed to continuous light (CL) (23L: 1D), whereas the other group was exposed to intermittent light (IL) (1L: 3D). At 6 wks of age, within each light program, chickens were injected intravenously (iv.) with either 3 mg/kg BW LPS, or with sterile saline. Blood samples were collected at 0, 3, 12 and 24 h post-injection. Total white blood cells (WBC), at 3, 12 and 24 h, were significantly higher in the IL-LPS group compared to the CL-LPS group. Body temperature and plasma corticosterone concentration at 3 and 12 h, were significantly lower in the IL-LPS group, compared to the CL-LPS group. Interleukin-1-like activity and IL-6 concentration were significantly lower in the IL-LPS group compared to the CL-LPS group at 3, 12 and 24 h. In the second experiment, 6 wk-old broiler chicks raised under CL, were divided into three groups. The first group was injected i.v. with 40 mg/kg BW melatonin, followed by 3 mg/Kg BW LPS 1 hour later. The second group was injected with saline followed by LPS 1 hour later. The third group received two saline injections 1 hour apart. Blood samples were collected at 0, 3, 12 and 24 h after the second injection. T lymphocyte proliferation were significantly higher in the melatonin-LPS group compared to the saline-LPS group. Plasma corticosterone concentration and body temperature were significantly lower in the melatonin-LPS group compared to the saline-LPS group at 3 h. IL-1-like activity and IL-6 concentration were significantly higher in the saline-LPS group compared to the other two groups at 3 and 12 h post injection. Total WBC was significantly higher in the melatonin-LPS group compared to the saline-LPS group at 12 and 24 hr. Our results indicate that intermittent light and melatonin injection can enhance the immune response and reduce the inflammation induced by LPS injection.